Adaptaciones curriculares para estudiantes con TDAH en Unidad Educativa Padre Juan de Velasco de la ciudad de La Victoria, periodo lectivo 2023-2024. - Iñiguez Zaruma, Nathaly Gissell (2024)
The main aim of this curricular integration paper was to analyse the curricular adaptations applied on students with the ADHD syndrome at the Unidad Educativa Padre Juan de Velasco. It was an inductive, non-experimental, qualitative study. The researcher applied an interview, which was validated by the institution; after obtaining the results, a guide of strategies entitled ‘Learning without Limits: Curricular Adaptations for Students with ADHD in the Unidad Educativa Padre Juan de Velasco’, this proposal arises as a response to the need identified through research conducted in the Unidad Educativa Padre Juan de Velasco, which evidenced the existence of a significant number of students with ADHD who require curricular adaptations and specific support strategies to achieve effective learning. A post-test was then applied to show the level of knowledge regarding the ADHD syndrome and curricular adaptations, which was good in terms of the knowledge of the teaching staff. It is concluded that properly implemented curricular adaptations give fruitful results in the educational development of students with ADHD in the educational institution.